2001
DOI: 10.1109/22.903096
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cylindrical waveguide discontinuities using vectorial eigenmodes and perfectly matched layers

Abstract: Abstract-In this paper, we analyze the scattering at discontinuities in cylindrical waveguides, starting from a vectorial eigenmode expansion and by introducing perfectly matched layer (PML) boundary conditions. The structure under study is enclosed in a metal cylinder to discretize the radiative mode spectrum, while the coating of this cylinder with PML vastly reduces the influence of parasitic reflections at the metal. This allows for a model that is both faster and more accurate than previous models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 16 publications
(18 reference statements)
0
54
0
Order By: Relevance
“…Let us now consider the configuration shown in Figure 2, consisting of a circular dielectric waveguide with a core section having refractive index n co , permeability co , and radius r. The cladding, with refractive index n cl and permeability cl , is terminated by a PML with thickness ⌬ and absorption 0 , to form a closed circular waveguide with radius R. In [6,11] it is shown that, by stretching the coordinates, the air cladding can be combined with the PML to form a cladding layer with complex thickness R Ϫ r ϭ R Ϫ r Ϫ j⌬( 0 / 0 ). By replacing the real radius R of the closed circular waveguide by a complex complex radius R , one can easily perform the modal analysis of the waveguide under consideration.…”
Section: The Circular Dielectric Waveguidementioning
confidence: 99%
See 3 more Smart Citations
“…Let us now consider the configuration shown in Figure 2, consisting of a circular dielectric waveguide with a core section having refractive index n co , permeability co , and radius r. The cladding, with refractive index n cl and permeability cl , is terminated by a PML with thickness ⌬ and absorption 0 , to form a closed circular waveguide with radius R. In [6,11] it is shown that, by stretching the coordinates, the air cladding can be combined with the PML to form a cladding layer with complex thickness R Ϫ r ϭ R Ϫ r Ϫ j⌬( 0 / 0 ). By replacing the real radius R of the closed circular waveguide by a complex complex radius R , one can easily perform the modal analysis of the waveguide under consideration.…”
Section: The Circular Dielectric Waveguidementioning
confidence: 99%
“…We consider an AlAs-AlOx waveguide-PML configuration with n co ϭ 2.9, n cl ϭ 1.55, r ϭ 0.5 m, R ϭ 1 m, and ⌬ ϭ 0.25 m at a free-space wavelength of ϭ 1 m. A strongly absorbing PML is obtained for R ϭ (1.0 Ϫ 0.1j) m. The parameters of this configuration correspond to the VCSEL resonator studied in [6].…”
Section: Vcsel Cavitymentioning
confidence: 99%
See 2 more Smart Citations
“…Of special relevance and interest to the material herein is a series of papers on the spectral properties of PMLs [5,6,11,32], which explore the characteristics of the eigenvalues of continuous PMLs -i.e. without discretization errors-in the context of electromagnetic waves in the frequency domain.…”
Section: Introductionmentioning
confidence: 99%